Use of semi-coke as Pb ion adsorbent from polluted industrial wastewater - Hassan Koohestani; Abolfazl Gohariyan Bajestani (Journal of Applied Research in Water and Wastewater)
Due to the increase in water pollution, especially heavy metals, many ways have been proposed to absorb and remove them. So far, various adsorbents have been used to remove pollutants. Semi-coke, a carbonaceous material, is susceptible to use as an adsorbent due to its unique properties, such as good specific surface area and porosity. Therefore, in this study, it was added to a solution containing lead ions after preparing semi-coke particles. The effect of various parameters such as pH, adsorbent dosage, and contact time on the ability of semi-coke to absorb lead ions was investigated. The results showed that semi-coke has a negative surface charge so that it can absorb small ions on its surface by an electrostatic attraction. The optimal pH values, adsorbent dosage, and contact time were obtained by investigating the results as 5, 2.0 g, and 60 min, respectively. Under optimal conditions, semi-coke could absorb 94 % of lead ions from the solution.